“A new labour era?”: Canadian National Railways and the Railway Worker, 1919-1929 - Seager, Allen (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1992)
AbstractIt is conventional to assume that the idea of a 'new era of collaboration among organized labour, capital, and the slate in wartime Canada died still-born with the events at Winnipeg in 1919 and the Big Business assault on trade unionism during the 1920s. This paper suggests that the conventional picture has been overdrawn. Railway workers, and those in the public sector in particular, remained highly unionized, while their organizations became deeply enmeshed in structures of conciliation, arbitration, and 'co-operation' during the period 1919-1929. Under the leadership of President Henrx Thornton, the state-owned Canadian National Railways, the largest employer in Canada at that time, developed a unique strategy of labour-management collaboration seen in some quarters as the harbinger of a 'new labour era' for North American industry as a whole.